The relationship between basic psychological needs satisfaction and personal growth initiative among female college students in Western China: a chain mediation effect - Song, Shangxia; Yan, Bihua (Frontiers in Psychology, 2025)
IntroductionFocusing on the growth motivation of female college students in the resource-constrained environments of Western China, this study integrates perspectives from Self-Determination Theory and Positive Psychology to examine the relationship between basic psychological needs satisfaction and personal growth initiative, as well as the underlying mechanisms.MethodsBased on convenience sampling, a survey was conducted among 473 female college students with household registration in Western China who were studying at universities in the same region (M = 20.18, SD = 1.26; 70.6% were from rural areas). The survey employed the Basic Psychological Needs Scale, Personal Growth Initiative Scale, Positive Psychological Capital Questionnaire, and Future Time Perspective Scale.ResultsThis study found that among female college students in Western China, basic psychological needs satisfaction significantly and positively predicted psychological capital, future time perspective, and personal growth initiative. Psychological capital and future time perspective significantly and positively predicted personal growth initiative. Mediation analysis revealed that psychological capital and future time perspective played a chain mediation role between basic psychological needs satisfaction and personal growth initiative among female college students in Western China.DiscussionThis study reveals key mechanisms of personal growth among female college students in Western China within resource-limited environments. Basic psychological needs satisfaction can enhance personal growth initiative through multiple mediation pathways involving psychological capital and future time perspective. This provides a theoretical basis and practical direction for targeted interventions and subsequent empirical research. Education policies should focus on fulfilling students’ needs for autonomy, competence, and relatedness, while mental health services should attend to students’ levels of psychological capital and future time perspective.